Influence Plastic Polyethylene Terephthalate as Strong Adhesive Press Paving Block - Rosalin Delia; Gunaedy Utomo; Andi Marini Indriani (Potensi: Jurnal Sipil Politeknik, 2025)
As the population growth and human needs rise, the amount of plastic product waste was increase. Polyethylene Terephthalate (PET) plastic waste is difficult to naturally decomposed, but it can be recycled by using it as a mixture for paving blocks. Paving blocks, commonly utilized in urban infrastructure, present an opportunity for incorporating recycled materials, addressing environmental concerns while maintaining structural integrity. Therefore, this study aims to assess the effectiveness of PET as adhesive and partial replacement for cement in paving block mixtures. Compressive strength was conducted according to SNI 03-0691-1996 standards on paving block containing PET plastic. The experimental test was conducted at the Civil Engineering laboratory of Balikpapan University. The test was carried out using three different mixture compositions, including 30% PET : 70% sand, 40% PET : 60% sand, and 50% PET : 50% sand. The compressive test result showed that mixture of 30% PET: 70% sand produced the highest average compressive strength of 15.87 MPa, which meets the C quality standard and is suitable for pedestrian use. Meanwhile, a mixture of 50% PET: 50% sand produced an average compressive strength of 10.0 MPa, which meets the D quality and is suitable for parks and other uses.